Exploring the role of community pharmacies as a harm reduction environment for anabolic-androgenic steroid consumers: triangulating the perspectives of consumers and pharmacists - Timothy Piatkowski; Sarah Benn; Lkhagvadulam Ayurzana; Michelle King; Sara McMillan; Laetitia Hattingh (BMC, 2024)
Abstract Background While community pharmacies have been successful in providing harm reduction support for illicit substance consumers, little research has explored their role in addressing the needs of anabolic-androgenic steroid (AAS) consumers. Objective This study aimed to triangulate the attitudes and experiences of AAS consumers and community pharmacist's regarding AAS harm reduction. Methods Semi-structured interviews were conducted with AAS consumers (n = 8) and community pharmacists (n = 15) between December 2022 and August 2023 in Australia. Interview data were analysed using reflexive thematic analysis. Results While consumers emphasised easy access to pharmacies, particularly in urban areas, challenges were noted in rural regions. AAS consumers expressed a preference for community pharmacies, perceiving them as less confronting and a feasible avenue for accessing professional advice, highlighting the potential role of pharmacists in nurturing therapeutic alliances with AAS consumers. Similarly, pharmacists expressed receptivity to providing harm reduction information but acknowledged knowledge gaps, suggesting a need for tailored education programs to support AAS consumers effectively. Conclusions Community pharmacies can be an important environment for AAS harm reduction. Strategies include utilising private spaces for open discussions with AAS consumers and enhancing pharmacists' understanding of AAS to foster trust and support. Further research is needed to address knowledge gaps and training needs for pharmacy staff, with the aim of creating a safer environment for AAS consumers.